2002
DOI: 10.1002/1521-3765(20020517)8:10<2370::aid-chem2370>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Octahedral Bipyridine and Bipyrimidine Dioxomolybdenum(VI) Complexes: Characterization, Application in Catalytic Epoxidation, and Density Functional Mechanistic Study

Abstract: Complexes of the general formula [MoO2X2L2] (X=Cl, Br, Me; L2=bipy, bpym) have been prepared and fully characterized, including X‐ray crystallographic investigations of all six compounds. Additionally, the highly soluble complex [MoO2Cl2(4,4′‐bis(hexyl)‐2,2′‐bipyridine)] has been synthesized. The reaction of the complexes with tert‐butyl hydroperoxide (TBHP) is an equilibrium reaction, and leads to MoVI η1‐alkylperoxo complexes that selectively catalyze the epoxidation of olefins. Neither the Mo−X bonds nor th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
102
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 237 publications
(115 citation statements)
references
References 37 publications
13
102
0
Order By: Relevance
“…Also, a comparison between DRS spectra of the catalyst before and after epoxidation process shows no change (Figure 8). Considering the conversion results, solvent optimization and the literature, [38] it seems that the proposed mechanism proceeds via a seven-coordinate intermediate (Scheme 2). In respect to the mechanism in Scheme 2, it may the competition between methanol, acetonitrile as a coordinator solvent and (CH 3 ) 3 COO − in coordination to Mo(VI) in step (II) that causes a marked decrease in the catalyst activity.…”
Section: Epoxidation Of Olefins Catalysed Bymentioning
confidence: 98%
“…Also, a comparison between DRS spectra of the catalyst before and after epoxidation process shows no change (Figure 8). Considering the conversion results, solvent optimization and the literature, [38] it seems that the proposed mechanism proceeds via a seven-coordinate intermediate (Scheme 2). In respect to the mechanism in Scheme 2, it may the competition between methanol, acetonitrile as a coordinator solvent and (CH 3 ) 3 COO − in coordination to Mo(VI) in step (II) that causes a marked decrease in the catalyst activity.…”
Section: Epoxidation Of Olefins Catalysed Bymentioning
confidence: 98%
“…Previous studies with complexes of the type MoO 2 Cl 2 L bearing bipyridine ligands (L) have consistently indicated that neither the Mo-Cl bonds nor the Mo-N bonds are disrupted during catalytic olefin epoxidation using TBHP in decane as the oxidant [36,37]. The available experimental and theoretical evidence indicates that the complexes undergo an equilibrium reaction with excess TBHP to give seven-coordinate Mo VI g 1 -alkylperoxo complexes; attempts to isolate these species have been unsuccessful, with the starting compound always being recovered unchanged [36,37]. For complex 4, the fact that the selectivity to the epoxide is always 100% for both catalytic runs is consistent with the complex being stable under the reaction conditions.…”
Section: Catalytic Performance Of 1-3 Using Tbhp As Oxidantmentioning
confidence: 99%
“…Catalyst 1 (initial activity 272 mol·mol Mo -1 ·h -1 ) is much more active than 2 (initial activity 12 mol·mol Mo -1 ·h -1 ), and after 3 h the epoxide was obtained in quantitative yield in the presence of 1, whereas for 2 the conversion was still only 22%. The observed catalytic activity of 2 is comparable to that of other distorted octahedral Mo VI complexes of the type MoO 2 X 2 L (X = Cl, Br) bearing bidentate N-donor ligands (L) such as ethylenediimine [10], bipyridine [11] and bipyrimidine [12]. For compound 1, the reaction rate decreases drastically with time.…”
Section: Catalysismentioning
confidence: 99%
“…In general, the mechanisms proposed for t-BuOOH-based epoxidations of olefins with Mo VI complexes are heterolytic in nature, involving coordination of the oxidant to the metal centre (by the terminal oxygen of -OOtBu in the case of the complexes MoO 2 X 2 L with X = Cl, Br or Me, and L = Lewis base N-or O-ligand), which acts as a Lewis acid thereby increasing the oxidising power of the peroxo group, and subsequently the olefin is epoxidised by nucleophilic attack on an electrophilic oxygen atom of the oxidising species [8,11]. The rapid decrease in the olefin conversion rate has been attributed to the formation of tertbutanol (t-BuOH), a by-product of the epoxidation, that acts as a competitor to t-BuOOH for coordination to the metal centre, leading to the formation of inactive species [11,12]. The solvent effect was studied for compounds 1 and 2 using 1,2-dichloroethane, n-hexane or acetonitrile, at 55 ºC.…”
Section: Catalysismentioning
confidence: 99%